(untitled) (Bangladesh Agronomy Journal, 2016)
An experiment was conducted at the Bangladesh Rice Research Institute (BRRI), Gazipur during Boro season of 2013-14 and 2014-15 to find out the nitrogen use efficiency and yield of boro rice var. BRRI dhan28 and BRRI dhan29 under four N management practices such as application of prilled urea using prilled urea applicator, application of USG (2.7gm) using USG applicator, broadcasting of prilled urea following three splits and a control (without urea). The experimental design was RCBD replicated thrice. BRRI dhan29 with urea broadcasted plots produced higher grain yield (7.38t ha-1) followed by BRRI dhan29 with USG application (6.65 t ha-1). Hand broadcasting with urea fertilizer showed 15.38.5and 2.5, 9.89% higher grain yield than machine application of prilled urea and USG in BRRI dhan28 and BRRI dhan29, respectively. Grain yield showed a significant quadratic response to N fertilization and significant linear response with total dry matter production in both the varieties. Higher total N was uptake from urea broadcasted plots in BRRI dhan29 followed by urea broadcasted from BRRI dhan28. BRRI dhan29 with Prilled urea applicator and BRRI dhan29 with USG treatment uptake intermediate nitrogen. N uptake in grain and total N uptake had a significant linear and quadratic response to N treatment in BRRI dhan28 and BRRI dhan29. Nitrogen use efficiency was higher in BRRI dhan29 compared to BRRI dhan28. Economic analysis showed that rice var. BRRI dhan28 and BRRI dhan29 with urea broadcast had the highest gross return of Tk.145145.00 and Tk. 158310.00 ha-1, respectively. However, the maximum cost (Tk. 151131) was involved for BRRI dhan29 with urea broadcasting, while the minimum with no urea fertilizer application for both the varieties. The highest marginal rate of return (MRR) (Tk.1146) was recorded from BRRI dhan28 with USG application using BRRI applicator. Bangladesh Agron. J. 2016, 19(1): 1-10